Patterns of genetic variation in a prairie wildflower, Silphium integrifolium, suggest a non‐prairie origin and locally adaptive variation. Issue 1 (29th January 2021) - Raduski, Andrew R.; Herman, Adam; Pogoda, Cloe; Dorn, Kevin M.; Van Tassel, David L.; Kane, Nolan; Brandvain, Yaniv
Abstract : PREMISE: Understanding the relationship between genetic structure and geography provides information about a species' history and can be used for breeding and conservation goals. The North American prairie is interesting because of its recent origin and subsequent fragmentation. Silphium integrifolium, an iconic perennial American prairie wildflower, is targeted for domestication, having undergone a few generations of improvement. We present the first application of population genetic data in this species to address the following goals: (1) improve breeding by characterizing genetic structure and (2) identify the species geographic origin and potential targets and drivers of selection during range expansion. METHODS: We developed a reference transcriptome as a genotyping reference for samples from throughout the species range. Population genetic analyses were used to describe patterns of genetic variation, and demographic modeling was used to characterize potential processes that shaped variation. Outlier scans for selection and associations with environmental variables were used to identify loci linked to putative targets and drivers of selection. RESULTS: Genetic variation partitioned samples into three geographic clusters. Patterns of variation and demographic modeling suggest that the species origin is in the American Southeast. Breeding program accessions are from the region with lowest observed genetic variation. CONCLUSIONS: This prairie species did not originate within the prairie. Breeding may be improved by including accessions from outside of the germplasm founding region. The geographic structuring and the identified targets and drivers of adaptation can guide collecting efforts toward populations with beneficial agronomic traits.